The Political Law of Land Procurement for Public Interest and Its Relevance to Indonesian Readiness in Facing the ASEAN Economic Community (Law Research Review Quarterly, 2015)
Legal politics is an effort to make law as a process of achieving the goals of the state. Land acquisition for public purposes is one of the state's efforts to realize people's welfare. Land acquisition is an effort to provide land for development, aimed at the interests of the nation, state and society. Textually, the politics of land acquisition law clearly manifests people's welfare, but at the implementation level there are still inconsistencies. This is evident from the practice of land acquisition both during the new order and reformation. Facing the ASEAN economic community, the legal politics of land acquisition will be tested in a practical level, whether consistent or shifted to the interests of investors.